Rational use of broiler chicken by-products and coagulated melange in the production of pates for healthy nutrition of the population of the regions of the Russian Federation - Borisova Veronika; Klimenkova Anastasia; Revyakin Artyom; Mikhailenko Ivan (BIO Web of Conferences)
The article is devoted to the development of a new type of enriched pate based on chicken liver and coagulated egg melange. The theoretical review studies the nutritional value of the main and additional raw materials used to produce pates, provides data on the nutritional value of the enriching raw material used to increase the physiological value of the developed pates - the biologically active additive “Ecoferrin”. Flaxseed oil is added to the pate to increase biological efficiency. The practical part of the article presents the results of a study of the organoleptic properties of new types of pates from chicken liver with the addition of coagulated melange in various proportions, flaxseed oil and the biologically active additive “Ecoferrin”. The content of proteins, fats, carbohydrates, iron in the developed pates and their energy value are determined by the calculation method.